The incorporation of computer-aided learning (CAL) material for medicinal chemistry teaching in peripheral nervous system courses (PHC 452) / Mohamad Hanif Mohd Kashim - Mohd Kashim, Mohamad Hanif (2013)
In pharmacy education, Medicinal Chemistry is unique subject, vital knowledge and critical-thinking skill which make pharmacist as chemical expert among health care provider. Since the Medicinal Chemistry focusing on drug molecules and its therapeutic application in clinical, it is important for student to visualize as three-dimension objects. However, lecture based learning or tradition teaching method unable student to visualized drug molecular and offer better understanding. Thus, increase burden to educator to finds other teaching method to deliver Medicinal Chemistry more efficient and attractive. From the result, 88.61 % of respondents think CAL can help understanding each chapter in Medicinal Chemistry and 89.7% of respondents stated that incorporation of CAL material with lecture-based will help student batter understanding. The incorporation of computer-aided learning in teaching medicinal chemistry provide alternative teaching method and adjunct to lecture which is important tool to increase student understanding in medicinal chemistry.